31 Remote myocardial fibrosis predicts adverse outcome following myocardial infarction. (28th January 2023) - Bradley, Joshua; Bradley, J; Schelbert, EB; Bonnett, LJ; Lewis, GA; Lagan, J; Orsborne, C; Brown, PF; Black, N; Soltani, F; Fröjdh, F; Ugander, M; et al.
Abstract : Introduction: Heart failure (HF) most commonly occurs in patients with prior myocardial infarction (MI), but factors other than MI size may be deterministic. Fibrosis of myocardium remote from the MI is associated with adverse remodelling. This study aimed to: 1) Investigate the association between remote myocardial fibrosis (RMF) measured using cardiovascular magnetic resonance (CMR) extracellular volume (ECV), and HF and death following MI; and 2) Identify predictors of RMF post-MI, and determine the relationship with infarct size. Materials and Methods: Multicentre prospective cohort study of 1, 199 consecutive patients undergoing CMR with evidence of MI on late gadolinium enhancement. Median follow-up 1, 133 (895–1, 442) days. Cox regression was used to identify factors predictive of the primary outcome; a composite of first hospitalisation for HF (HHF) or all-cause mortality, post-CMR. Linear regression was used to identify determinants of remote ECV. Results: RMF was a strong predictor of primary outcome (χ 2 : 15.6, HR: 1.07 per 1% increase in ECV, 95% CI: 1.04–1.11, p=0.00011), and was separately predictive of both HHF and death. Left ventricle end systolic index (LVESVi) and infarct size were not associated with adverse outcome after multivariable adjustment. The strongest predictors of remote ECV were diabetes, sex, natriuretic peptides and body mass index (adjusted model R 2 =0.283). The relationship between infarct size and remote ECV was very weak. Discussion: RMF is a strong predictor of adverse outcomes following MI, and is more strongly predictive than infarct size, and other metrics of ventricular structure (LVESVi). Moreover, RMF was minimally associated with infarct size, and only 28% of the variance in RMF could be explained, despite extensive phenotyping. This study raises the possibility that anti-fibrotic therapies aimed at inhibiting RMF formation may reduce adverse remodelling and improve outcomes post-MI. Finally, this study raises the question of whether ECV may be more informative than LVESVi as a measure of remodelling in post-MI phase II trials, given ECV's mechanistic insight and stronger association with outcome. Conclusion: RMF, measured using ECV, is a strong predictor of HHF and death following MI. The mechanisms underlying RMF formation post-MI remain poorly understood, but factors other than infarct size appear to be important. Acknowledgements: The study was funded by the UK National Institute for Health Research (NIHR, CS-2015–15–003), and supported by a research grant from Guerbet Laboratories Limited. Immunoassay testing equipment and materials were gifted by Roche Diagnostics International Limited. The work was also supported in part by a British Heart Foundation Accelerator award to The University of Manchester (BHF, AA/18/4/34221). NIHR, BHF, Guerbet Laboratories Limited and Roche Diagnostics International Limited had no role in the study design, data collection, data analysis, data interpretation, or writing of the report. The corresponding author had full access to all the data in the study and had final responsibility for the decision to submit for publication. Guerbet Laboratories Limited and Roche Diagnostics International Limited conducted a factual accuracy check of the manuscript, but any decisions to incorporate comments were made solely at the discretion of the authors.